Revisiting Bond Breaking and Making in EuCo2P2: Where are the Electrons?. Issue 23 (18th March 2019) - Yannello, Vincent; Guillou, Francois; Yaroslavtsev, Alexander A.; Tener, Zachary P.; Wilhelm, Fabrice; Yaresko, Alexander N.; Molodtsov, Serguei L.; Scherz, Andreas; Rogalev, Andrei; Shatruk, Michael
Abstract: Invited for the cover of this issue are the groups of Michael Shatruk at Florida State University, Andrei Rogalev at the European Synchrotron Radiation Facility, and colleagues. The image depicts the detective work by the authors while trying to interpret their experimental results. Read the full text of the article at10.1002/chem.201900244 . Abstract : " The concept of formal oxidation states is frequently used by chemists to achieve an adequate understanding of correlations between the composition, structure, and properties of molecules and materials. In this work, we demonstrate that such formal charges become inadequate when one deals with metallic systems with delocalized bonding, where electronic states of different elements are strongly mixed ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 5865 ff. (DOI:10.1002/chem.201900244 ).